2018
DOI: 10.17765/2176-9168.2018v11n1p301-326
|View full text |Cite
|
Sign up to set email alerts
|

O Soro Do Leite, Seus Principais Tratamentos E Meios De Valorização

Abstract: Questões ambientais, associadas à produção de soro do leite pelas agroindústrias de laticínios, impulsionam buscas por alternativas que visem tanto a preservação do meio ambiente, quanto a agregação de valor a esse coproduto. Este artigo tem como objetivo discutir as vantagens, desvantagens, oportunidades e ameaças dos principais tratamentos e meios de valorização do soro do leite. Desta forma, a revisão de literatura apresenta como resultado uma discussão crítica sobre o contexto geral da empregabilidade atua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
10
0
5
Order By: Relevance
“…A previous study has reported that about 40% whey produced in Brazil was inappropriately discarded, mainly by small and medium-sized companies (Marquardt et al, 2012), indicating an evolution in relation to this aspect. On fact, whey is a harmful waste to the environment and can cause great impact and damage to the fauna and flora, once its Biochemical Dxygen Demand (Nunes et al, 2018). Dur results suggest an improvement in awareness regarding the negative impact caused by the whey disposal in the environment.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous study has reported that about 40% whey produced in Brazil was inappropriately discarded, mainly by small and medium-sized companies (Marquardt et al, 2012), indicating an evolution in relation to this aspect. On fact, whey is a harmful waste to the environment and can cause great impact and damage to the fauna and flora, once its Biochemical Dxygen Demand (Nunes et al, 2018). Dur results suggest an improvement in awareness regarding the negative impact caused by the whey disposal in the environment.…”
Section: Resultsmentioning
confidence: 96%
“…Dur results suggest an improvement in awareness regarding the negative impact caused by the whey disposal in the environment. Ot was reported that relatively high volume of whey is discharged, that it can brings several environmental damages and depletion of the effluent treatment system if not treated properly (Nunes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that about 40% of the whey produced in Brazil is improperly discarded, mainly by small and medium-sized enterprises, becoming a harmful industrial waste to nature that causes a high negative environmental impact, due to the damage it offers to fauna and flora, because its Biochemical Oxygen Decomposition (DBO) is about 100 times higher than that of domestic sewage (HARAGUCHI et al, 2006;ROHLFES et al, 2011;GAJO et al, 2017;NUNES et al, 2018).…”
Section: Rc: 96244mentioning
confidence: 99%
“…O soro de leite consiste em um coproduto lácteo das indústrias de laticínios que é extraído da coagulação do leite no processo fabril de queijos (Nunes et al, 2018). O soro é um composto rico em carboidratos (lactose) e seu descarte de forma inadequada gera diversos impactos ambientais.…”
Section: Introductionunclassified